To solve this equation, we will start by simplifying both sides of the equation.
On the left side of the equation:
3(b-2) + 5 can be simplified using the distributive property as follows:
3 * b + 3 * (-2) + 5 = 3b - 6 + 5 = 3b - 1
On the right side of the equation:
7 + 3(2b-5) - 38 can be simplified using the distributive property as follows:
7 + 6b - 15 - 38 = 6b - 46
So, the equation becomes:
3b - 1 = 6b - 46
Now, we will collect like terms on one side of the equation.
Subtracting 6b from both sides, we have:
3b - 6b - 1 = 6b - 6b - 46
-3b - 1 = -46
Now, we will isolate the variable by adding 1 to both sides:
-3b -1 + 1 = -46 + 1
-3b = -45
Finally, we will solve for b by dividing both sides by -3:
-3b/-3 = -45/-3
b = 15
Therefore, the solution to the equation is b = 15.
3(b-2)+5=7+3(2b-5)-38
1 answer